Research progress on the regulatory effects and mechanisms of natural active products on intestinal barrier function - Zheng, Fuyixuan; Sun, Yuemei; Zhao, Minghui; Wang, Rong; Li, Wenbin (Frontiers in Pharmacology, 2025)
As a key defense line for the body to resist pathogens and maintain internal environment stability, the intestinal barrier is crucial for maintaining human health, and its functional damage is closely related to the occurrence of various intestinal diseases, especially in the hypoxic environment of high altitude, the problem of intestinal barrier damage is more prominent. Natural active products are widely sourced and exhibit unique potential in regulating intestinal barrier function due to their multi-target and low-toxicity characteristics. This article comprehensively reviews the prevention and treatment effects of natural active products on common intestinal diseases and high-altitude intestinal injury, focusing on elucidating the mechanism by which they regulate intestinal barrier function through eight key signaling pathways such as NF-κB, Wnt/β-catenin, and mTOR, in which the HIF family is a key factor in regulating hypoxic stress response, and this signaling pathway is the “lifeline” for cells to cope with hypoxia, emphasizing its application potential in the prevention and treatment of high-altitude intestinal barrier injury, and providing a theoretical basis for the development of natural drugs for high-altitude environments and related intestinal diseases.